Feminist speculations and the practice of research-creation writing pedagogies and intertextual affects. - Truman, Sarah E. (London : Routledge, 2021)
Feminist Speculations and the Practice of Research-Creation provides a unique introduction to research-creation as a methodology, and a series of exemplifications of research-creation projects in practice with a range of participants including secondary school students, artists, and academics. In conversation with leading scholars in the field, the book outlines research-creation as transdisciplinary praxis embedded in queer-feminist anti-racist politics. It provides a methodological overview of how the author approaches research-creation projects at the intersection of literary arts, textuality, artistic practice, and pedagogies of writing, drawing on concepts related to the feminist materialisms, including speculative thought, affect theories, queer theory, and process philosophy. Further, it troubles representationalism in qualitative research in the arts. The book demonstrates how research-creation operates through the making of or curating of art or cultural productions as an integral part of the research process. The exemplification chapters engage with the author's research-creation events with diverse participants all focused on text-based artistic projects including narratives, inter-textual marginalia art, postcards, songs, and computer-generated scripts. The book is aimed at graduate students and early career researchers who mobilize the literary arts, theory, and research in transdisciplinary settings.
Keywords: Literature -- History and criticism -- Theory, etc; Creation (Literary, artistic, etc.); Research; Feminist theory; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research